2015
DOI: 10.5811/westjem.2015.1.21851
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Extrication versus the Kendrick Extrication Device (KED): Comparison of Techniques Used After Motor Vehicle Collisions

Abstract: IntroductionThe goal of this study was to compare application of the Kendrick Extrication Device (KED) versus rapid extrication (RE) by emergency medical service personnel. Our primary endpoints were movement of head, time to extrication and patient comfort by a visual analogue scale.MethodsWe used 23 subjects in two scenarios for this study. The emergency medical services (EMS) providers were composed of one basic emergency medical technician (EMT), one advanced EMT. Each subject underwent two scenarios, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…The time was significantly shorter using the rapid extraction for all the patients, however the angles of rotation of the head were also greater. Therefore, in contrast to the previous study, in this experiment a decrease in the movement of the patient's neck was shown using the Kendrick® extractor [21,26].…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The time was significantly shorter using the rapid extraction for all the patients, however the angles of rotation of the head were also greater. Therefore, in contrast to the previous study, in this experiment a decrease in the movement of the patient's neck was shown using the Kendrick® extractor [21,26].…”
Section: Discussioncontrasting
confidence: 62%
“…This trial reports that it causes more movement in the spine than a "self-excision" of the patient wearing a cervical collar. This issue was also addressed by Bucher, et al [26], who compared the application of Kendrick® with rapid extraction by emergency services professionals. The sample consisted of 23 subjects in two scenarios: One using rapid extraction without using the Kendrick® and the other involving said device.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This should be done with a Kendrick device (KED) [18]. If properly installed, it is sufficient to immobilize the head when an orthopaedic collar is also used [19,20], as well as the chest and pelvis of the injured person. It has several belts that are fastened in the right order: first the middle chest belt, lower chest belt, hip belts, then head stabilizing belts, and finally the upper chest belt.…”
Section: Instrumented Means Of Evacuation Of An Injuredmentioning
confidence: 99%
“…[15][16][17] Similarly, numerous test trials have attempted to quantify the effects of spinal motion associated with various devices and reported little or no significant differences. [15][16][17][18][19] In addition, in 2005, Kwan and Bunn 18 reported a lack of randomized controlled trials among trauma patients on the effects of spinal immobilization on primary or secondary neurological injuries.…”
mentioning
confidence: 99%